1991
DOI: 10.1002/1097-0142(19910601)67:11<2741::aid-cncr2820671105>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

In vitro radiation resistance among cell lines established from patients with squamous cell carcinoma of the head and neck

Abstract: Twenty-five squamous cell carcinoma (SCC) cell lines from 20 patients with head and neck cancer were assessed for radiosensitivity in vitro using a 96-well plate assay. Four non-SCC lines were also tested. Radiation sensitivity of individual cell lines was compared using the area under the survival curve (AUC) as a measure of the mean inactivation dose. Tumor lines were tested with either a cobalt-60 (%o) 7-irradiator having a dose rate of 100 cGy/minute or with a 4-meV photon beam having a dose rate of 200 cG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 12 publications
2
51
0
Order By: Relevance
“…Irradiation assay Radiosensitivity assay. Radiosensitivity of all cell lines was tested with a 96-well plate clonogenic assay, developed by Gr enman and colleagues (23,24). The radiosensitivity of a cell line was defined as the area under the survival curve, with measurements of the survival fraction at 6 different doses, each repeated at least 3 times.…”
Section: Methodsmentioning
confidence: 99%
“…Irradiation assay Radiosensitivity assay. Radiosensitivity of all cell lines was tested with a 96-well plate clonogenic assay, developed by Gr enman and colleagues (23,24). The radiosensitivity of a cell line was defined as the area under the survival curve, with measurements of the survival fraction at 6 different doses, each repeated at least 3 times.…”
Section: Methodsmentioning
confidence: 99%
“…On the same model cells we compared the proliferation before and after retinoid therapy as well as the expression of several retinoid receptors, from Ki-67 and p53. We used the two HNSCC cell lines UM-SCC-14C and UM-SCC-35 (119,120) and controlled with the spontaneously immortalized aneuploid human keratinocyte cell line HaCaT (121). The doubling time of UM-SCC-35 is between 38 (122) and 52 h (123), of UM-SCC-14 C it is ~26 h (119,120,123).…”
Section: Introductionmentioning
confidence: 99%
“…Schroeder and Zouboulis (128) were also able to demonstrate dose-dependent inhibition of growth in HaCaT-cells, more clearly by 13-cRA than by ATRA. (119,120) isolated the tumor cell lines from fresh head and neck cancer tissues: UM-SCC-35 for a primary tonsil carcinoma (T4N1M0, moderately well differentiated) and UM-SCC-14C for a skin metastasis of a floor and mouth carcinoma (poorly differentiated) after chemotherapy. The spontaneously immortalized aneuploid human keratinocyte cell line HaCaT was established by Boukamp et al (121) from the tumor-free skin area surrounding a melanoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of a variety of tumor as well as normal cell lines have shown a wide range of radiosensitivities among different tissues as well as within a certain histological tumor entity [1,2]. Exposure of the cell to ionizing radiation results in a wide range of different DNA lesions, including single-and doublestrand breaks.…”
Section: Introductionmentioning
confidence: 99%